The bipolar disorder over-diagnosis trend – in brief - Olajossy-Hilkesberger, Luiza; Olajossy, Marcin (Current Problems of Psychiatry, 2011)
Recently, the discussion about the over-diagnosis of the bipolar disorder and other conditions with psychotic features has been taking place among the psychiatrists. Because the mood stabilizers to treat mental conditions with the broad spectrum of the affective component are prescribed more and more nowadays, the tendency to over-diagnose a bipolar disorder seems to be present. The existing problem with the coverage provided by the National Health Insurance Agency also contributes to the picture.The authors remind us about the presently valid diagnostic criteria for this condition, discuss the possible reasons for the over-diagnosis phenomenon and present the opposite scientific approaches, views and opinions. At the end, they come to the conclusion that the near future might bring some revisions to the bipolar disorder definition and diagnostic criteria. The inclusion of the biomarkers as well as “the dimension concept” in the diagnostic system will alter it even further.